Performance of Mid-Size Internationalized Indian Firms: Evaluating the Role of Family Control - Ahsan , Faisal M; Singal, Ajay (Asian Journal of Empirical Research, 2019)
The rapidly growing and gradual emergence of multinational firms from the Indian sub-continent now calls for thorough re-understandings of extant theories and existing ideologies of the ‘internationalization’ process. We would initially assess the three-stage model of internationalization in the context of mid-size Indian firms and intend to investigate the relationship between performance and degree of internationalization. Based on the longitudinal dataset (2005-12) of publicly listed firms, our findings suggested that mid-size firms remained stuck up in the first stage of internationalization and accordingly exhibit a downward-sloping relationship between internationalization’s degree and performance. Most of the mid-size firms continued to show a predominantly family-controlled stance, and the impact of family ownership shows negative effects on the degree of internationalization. By examining the performance heterogeneity in family-owned firms towards internationalization, this paper enriches the existing body of research and assume it to be a prolific addition in the literature on international expansion.